The Role of Internal Oversight Based on Fraud Risk Control in Enhancing Regional Financial Accountability - Geofanny Edo Pratama; Dian Ferriswara; Sarwani Sarwani; Sri Kamariyah (International Journal of Humanities and Social Sciences Reviews, 2026)
Regional financial accountability is a fundamental principle in good governance. However, the management of regional finances still faces various challenges, particularly related to the potential occurrence of fraud and the suboptimal functioning of internal control systems. This study aims to analyze the role of the Government Internal Supervisory Apparatus (APIP) in strengthening regional financial accountability through the implementation of internal oversight based on Fraud Risk Control. This research employs a qualitative approach using the Qualitative Secondary Analysis (QSA) method, which utilizes secondary data from various scientific literature, previous research findings, and policy documents relevant to internal oversight in the public sector. The results indicate that internal oversight is a crucial mechanism in preventing fraud in public sector financial management. The implementation of Fraud Risk Control plays a role in identifying, assessing, and controlling fraud risks, thereby enhancing the transparency and accountability of regional financial management. Furthermore, APIP has a strategic role through internal audit functions, risk-based oversight, and providing consultation to improve regional financial management systems. Strengthening APIP’s capabilities, enhancing the maturity of the Government Internal Control System (SPIP), and ensuring the independence of internal supervisors are essential factors in realizing transparent and accountable regional financial governance.